Tubular, lactating, and ductal adenomas are devoid of MED12 Exon2 mutations, and ductal adenomas show recurrent mutations in GNAS and the PI3K-AKT pathway - Volckmar, Anna-Lena; Leichsenring, Jonas; Flechtenmacher, Christa; Kirchner, Martina; Ridinger, Kathrin; Lorenz, Katja; Herpel, Esther; Schirmacher, Peter; Penzel, Roland; Endris, Volker; Stenzinger, Albrecht (Genes, chromosomes & cancer, 2017)
Adenomas of the breast are rare benign tumors although single cases with malignant behavior have been reported. However, the genetic basis of these tumors is unknown. Employing targeted next generation sequencing of 50 cancer-related genes as well as Sanger sequencing, we profiled a cohort of 18 mammary adenomas comprising 9 ductal, 6 tubular, and 3 lactating adenoma. Missense mutations were detected in 8 of the 18 cases (44%). Specifically, five (56%) ductal adenomas and three (50%) tubular adenomas harbored mutated genes. No mutations were detected in lactating adenomas. Three of the nine ductal adenomas showed mutant AKT1 (p.E17K) with two of them harboring an additional GNAS mutation (p.R201C). One case had mutant PIK3CA (p.H1047R) and another case a mutation in GNAS (p.R201C). The three cases of mutated tubular adenomas showed mutations in either MET or FGFR3. Of note, we did not detect copy number changes and none of the cases including tubular adenomas had mutations in exon 2 of MED12. Our results suggest that ductal adenomas are related to papillomas of the breast and screening for mutations in exon 2 of MED12 might help to facilitate differential diagnosis between tubular adenoma and fibroadenoma in difficult cases. Lastly, our data exemplarily demonstrate that mutations in cancer-related genes per se do not indicate malignancy but occur in benign tumors. © 2016 Wiley Periodicals, Inc.